Chapter 23: "Emergency feeding" in America: making words and deeds actually matter - Silverman, Greg (Edward Elgar Publishing, 2023)
Making change is never easy. In New York City, the largest in the United States with over eight million people, West Side Campaign Against Hunger (WSCAH) has focused on making sure all New Yorkers have access with dignity to a choice of healthy food and supportive services. Serving almost 75,000 people per year, WSCAH has a history of innovation in emergency feeding. From building a customer centric shopping experience almost three decades ago for its customers, to more recent community-based delivery, to advocacy efforts on the city and state level, to collective purchase models, WSCAH's efforts can be seen as a case study in testing out strategies to more impactfully and sustainably change the emergency feeding system in the United States and beyond.